Cold stress after swimming fatigue decreases immunity-related gene expression in the spleen of the Chinese sucker. Issue 122 (March 2022) - Qin, Chuanjie; Xie, Jiang; Shi, Xiaotao; Tan, Junjun
Abstract: For migratory fish, passing through the cold, fast flowing water of a dam causes stress, leading to disease and even death. To determine the immune response to cold stress in a dam-lake after swimming fatigue in Chinese sucker ( Myxocyprinus asiaticus ), the spleen mRNA expression profiles in response to cold stress (CS) after fatigue stress (FS) were compared with that of the control (SS). We identified 40, 952 differentially expressed genes (DEGs) in the spleen for at least one comparison among 211, 397 unigenes. We identified 11, 869 DEGs (4, 968 upregulated and 6, 901 downregulated), 17, 803 DEGs (10, 610 upregulated and 7, 193 downregulated), and 30, 579 DEGs (20, 652 upregulated and 9, 927 downregulated) in the SS vs. FS, SS vs. CS, and FS vs. CS comparisons, respectively. Enrichment analysis indicated the involvement of the immune system and infectious diseases, including the toll-like receptor pathway, the complement and coagulation cascade, and the natural killer cell-mediated cytotoxicity pathway. There were 2, 991 DEGs (271 upregulated and 2, 720 downregulated), and 2, 878 DEGs (873 upregulated and 2, 005 downregulated) associated with these pathways in the SS vs . FS and SS vs . CS comparisons, respectively. In the cold stress after fatigue group, the expression levels of heat shock protein (HSP) 70 and HSP90 genes were significantly upregulated; however, more immune response genes showed significantly downregulated expression in SS vs. CS compared with that in SS vs . FS, including those encoding tumor necrosis factor, C–C motif chemokines (3, 8, and 13), complement components (C3, C4, C6, and C7), immunoglobulin, and cathepsins. Overall, cold stress combined with swimming fatigue from passing the dam resulted in the downregulation of many immune genes, suggesting that the Chinese sucker might have experienced serious immune suppression. Highlights: 40, 952 spleen unigenes were identified from cold-stressed, fatigued Chinese sucker. The unigenes were associated with 21 immune system-related pathways. Differentially expressed genes were identified in the cold stress and fatigue groups. Cold stress after fatigue downregulated immune genes in the Chinese sucker spleen.